Analisis Pengaruh Motivasi, Mengikuti Pelatihan, Peran Kepemimpinan, dan Orientasi Pembelajaran terhadap Kinerja Karyawan: - Fierna Fajar Swasti; Didik Subiyanto; Epsilandri Septyarini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine the effect of work motivation, job training, leadership roles, and learning orientation on the performance of PT Daffa Jaya Utama employees. The research method uses quantitative. The population in this study were all employees of PT Daffa Jaya Utama as many as 50 employees. The sample used in this study were all 50 employees. The tests used in this research are validity, reliability, normality, heteroscedasticity, multicollinearity, multiple linear regression analysis, partial test, simultaneous test, and coefficient of determination test. The results showed that the variables of work motivation and leadership roles partially had no significant effect on employee performance, for job training and learning orientation variables partially had a significant effect on employee performance. Simultaneously the variables of work motivation, training, leadership roles, and learning orientation have a positive and significant impact on millennial children's investment interest Keywords: work motivation, job training, leadership roles, learning orientation, employee performance